FOSSIL 26AL AND 53MN IN THE ASUKA 881394 EUCRITE: EVIDENCE OF THE EARLIEST CRUST ON ASTEROID 4 VESTA - Nyquist L.E.; Reese Y.; Wiesmann H.; Shih C.Y.; Takeda H. (My University, 2003)
Asuka 881394 is a unique magnesian eucrite with pyroxenes that are Mg-rich like those of cumulate eucrites, but with a granulitic texture unlike the textures of cumulate eucrites. Plagioclase compositions are ~An98, and are even more calcic than those in cumulate eucrites. Pyroxene does not show pigeonite-to-orthopyroxene inversion textures, suggesting different crystallization conditions than those of cumulate eucrites. Mn-Cr isotopic analyses determined initial 53Mn/55Mn=(4.6+/-1.7)x10-6 and initial ε(53Cr)I=0.25+/-0.17 in A881394. This initial 53Mn abundance corresponds to a formation interval ΔtLEW=-6+/-2 Ma relative to the LEW86010 angrite, implying an 'absolute' age of 4564+/-2 Ma. Both the initial 53Mn abundance and the initial ε(53Cr)I value for A881394 are identical to those previously determined for the HED parent body at the time of its differentiation. Al-Mg isotopic analyses determined initial 26Al/27Al=(1.18+/-0.14)x10-6, from which a formation interval ΔtCAI=3.95+/-0.13 Ma is calculated relative to the canonical value 26Al/27Al=5x10-5 for CAI. Combining this formation interval with a recently reported Pb-Pb age of 4567.2+/-0.6 Ma for CAI gives 4563.2+/-0.6 Ma as the age of A881394, in excellent agreement with the age based on the Mn-Cr formation interval. Alternatively, the 53Mn and 26Al formation intervals of A881394 allow the Mn-Cr and Al-Mg timescales to be intercalibrated, suggesting that an 'absolute' CAI age of 4568 Ma is most consistent with the 4558 Ma Pb-Pb age of LEW86010. The initial 26Al abundance existing in A881394 would have been insufficient to cause global melting in the HED parent body (probably asteroid 4 Vesta). Nevertheless, it could have been derived by radioactive decay over only ~2 Ma from an abundance that would have been sufficient to cause global melting. The higher value of molar Mg/(Mg+Fe)=0.57 for A881394 than those of the ordinary (basaltic) eucrites (Mg/(Mg+Fe)=0.30-0.42) suggests additional factors may have been important for magma genesis on the parent body. If 26Al were the only heat source, partial melting would have been the major process in the interior of the parent body, and Mg/(Mg+Fe) would be lower in the melts than in the primordial source material. Late-stage accretion could have supplied relatively magnesian primordial material to the surface of the parent body, thereby increasing Mg/(Mg+Fe) in a shallow magma ocean from which A881394 crystallized, and also may have augmented 26Al heating. The granulitic texture of A881394 may have been produced during residence in the thin, earliest, crust, kept hot by the magma beneath it. If 26Al was, nevertheless, the major heat source for asteroidal melting, it may account for declining post-accretion heating of main belt asteroids with increasing heliocentric distance.
Keywords: EUCRITES; CHRONOLOGY; 26AL HEATING; 26AL TIMESCALE; 53MN TIMESCALE